Assessment of Population Knowledge and Awareness of Nursemaid’s Elbow in Children: A Cross-Sectional Study in Al-Baha Region, Saudi Arabia - Ramy Samargandi; Reem M Alharthi; Adham M Alghamdi; Miad A Alzahrani; Majdi H Alzahrani; Khalid A Alzahrani (Journal of Orthopaedic Case Reports)
Introdcution and Aims: Nursemaid’s elbow (NME) is a common pediatric upper-extremity injury affecting young children. In this study, we aim to assess the knowledge and awareness of the NME in children between population in Al-Baha region in Saudi Arabia. Materials and Methods: This is a cross-sectional study conducted among the population Al-Baha region, from February 2024 to April 2024, inclusion criteria include individuals living in Al-Baha, who are older than 18 years and agree to participate. We excluded those who are not willing to participate or not residing in Al-Baha and healthcare professionals. Data collection done via an online validated questionnaire in Arabic language. Statistical analyses were conducted using Chi-square test and Fisher’s exact test. A significance level of less than 0.05 (P < 0.05) was considered statistically significant. Results: 588 participants were included. Females were majority (69.6%), and the largest age group was 40–49 years old (34.7%). We found that (59.5%) of participants had not heard or read about NME. There were some misconceptions noted, such as (67.3%) who believed that both genders are equally affected and incorrect identification of symptoms (37.1%). The awareness of the case recurrence was (55.1%). Friends or family are the primary sources of information (18.2%). And lastly, (76.9%) of participants expressed a desire to learn more about NME. Conclusion: There is an obvious lack of knowledge about NME among population in the Al-Baha region, so more awareness campaigns for society are needed to raise the level of knowledge, and to prevent the occurrence and recurrence.